PENGARUH LKS BERORIENTASI MODEL KECERDASAN MAJEMUK TERHADAP KOMPETENSI FISIKA SISWA KELAS XI SMA NEGERI 2 PADANG - Devi Yenuar Rezki; Festiyed Festiyed; Asrizal Asrizal (Universitas Negeri Padang, 2015)
Learning in Education Unit Level Curriculum requires the innovative teaching materials to increase student competence. An alternative way to get it is student worksheet oriented multiple intelligences model. The goal of research is to detect student worksheet oriented model of multiple intelligences influence towards the student competence of the 11th grade in SMAN 2 Padang. This research is a quasi-experimental with Randomized Control Group Only Design. The sampling technique is purposive sampling. The result of research show that students learning outcomes in the cognitive, affective, and psychomotor domains respectively 81.28, 73.90, and 84.10. The use of student worksheet oriented multiple intelligences model has a significant impact on the physics students competence in cognitive, affective, and psychomotor domains